The D-score: a metric for interpreting the early development of infants and toddlers across global settings. Issue 6 (19th November 2019) - Weber, Ann M; Rubio-Codina, Marta; Walker, Susan P; van Buuren, Stef; Eekhout, Iris; Grantham-McGregor, Sally M; Araujo, Maria Caridad; Chang, Susan M; Fernald, Lia CH; Hamadani, Jena Derakhshani; Hanlon, Charlotte; Karam, Simone M; et al.
Abstract : Introduction: Early childhood development can be described by an underlying latent construct. Global comparisons of children's development are hindered by the lack of a validated metric that is comparable across cultures and contexts, especially for children under age 3 years. We constructed and validated a new metric, the Developmental Score (D-score), using existing data from 16 longitudinal studies. Methods: Studies had item-level developmental assessment data for children 0–48 months and longitudinal outcomes at ages >4–18 years, including measures of IQ and receptive vocabulary. Existing data from 11 low-income, middle-income and high-income countries were merged for >36 000 children. Item mapping produced 95 'equate groups' of same-skill items across 12 different assessment instruments. A statistical model was built using the Rasch model with item difficulties constrained to be equal in a subset of equate groups, linking instruments to a common scale, the D-score, a continuous metric with interval-scale properties. D-score-for-age z-scores (DAZ) were evaluated for discriminant, concurrent and predictive validity to outcomes in middle childhood to adolescence. Results: Concurrent validity of DAZ with original instruments was strong (average r =0.71), with few exceptions. In approximately 70% of data rounds collected across studies, DAZ discriminated between children above/below cut-points for low birth weight (<2500 g) and stunting (−2 SD below median height-for-age). DAZ increased significantly with maternal education in 55% of data rounds. Predictive correlations of DAZ with outcomes obtained 2–16 years later were generally between 0.20 and 0.40. Correlations equalled or exceeded those obtained with original instruments despite using an average of 55% fewer items to estimate the D-score. Conclusion: The D-score metric enables quantitative comparisons of early childhood development across ages and sets the stage for creating simple, low-cost, global-use instruments to facilitate valid cross-national comparisons of early childhood development.